Solidarity in Southeast European Swiss family networks during Covid-19 - Waldis, Barbara; Marques, Marta (Ревија за социјална политика/Journal of Social Policy, 2023)
Family solidarity in Southeast European Swiss families was challenged by the state border closures due to Covid-19. The interviewees in our exploratory study (2021, 2023) emphasize the additional geographical and emotional difficulties during the pandemic of staying connected with the seniors in the Southeast European countries, as well as the increased sense of obligation of care. For the families with senior citizens from the mentioned countries in Switzerland however, the question of family solidarity looks quite different due to the existing state social insurances. Within a situation of crisis, what happens to the much-cited family solidarity serving as a safety net in Southeast European countries in a situation of low social welfare? How can we compare these trans-European families caring for seniors across European borders with the care of those seniors within the welfare state of Switzerland? The qualitative, actor-centred content analysis of twelve family interviews is oriented by a decolonial social work perspective. The contribution therefore focuses on the action strategies of family members living in Switzerland vis-à-vis senior citizens living in Kosovo, Serbia or North Macedonia and contrasts these with the experiences of families with senior citizens from Southeast Europe in Switzerland. The experiences during the pandemic sharpen the comprehension for the challenges of a cross-border social policy, on the one hand regarding the importance of family solidarity in accordance of the family composition, and on the other hand regarding a network of solidarity rooted in public social institutions.